Levels and dietary exposure risk assessment of organophosphorus esters and polychlorinated biphenyls in pig liver from Hubei Province in 2022 - LIU Xiaofang; LIU Xiao; ZHOU Yan; CHEN Haichuan; CHENG Qingyun; CAO Wencheng; WEN Sheng (Zhongguo shipin weisheng zazhi)
ObjectiveTo investigate the levels of seven organophosphorus esters （OPEs） and six indicator polychlorinated biphenyls （PCBs） in pig liver from Hubei Province， the risk of exposure to OPEs and PCBs in Hubei residents through dietary intake of pig liver were assessed.MethodsA total of 51 pig liver samples were collected from Hubei Province in 2022. By isotope dilution method， OPEs and PCBs in pig liver samples were determined by ultra-high performance liquid chromatography tandem mass spectrometry （UPLC-MS/MS） and high resolution gas chromatography high resolution magnetic mass spectrometry （HRGC-HRMS）， respectively. The source of pollution was explored by analyzing the fingerprint characteristics. Based on the estimation dietary intake （EDI） and hazard index （HI） of Hubei residents， the risk of exposure to OPEs and PCBs through dietary intake of pig liver was assessed.ResultsThe levels of seven OPEs （∑7OPEs） in pig liver ranged from 15.6 to 262 ng/g， with an average of 89.7 ng/g （P50=88.4 ng/g）. The levels of six PCBs （∑6PCBs） ranged from 3.67 to 19.5 pg/g， with an average of 9.02 pg/g （P50=8.21 pg/g）. Tris （1，3-Dichloro-2-Propyl） Phosphate （TDCPP） and PCB 52 was the main characteristic pollutant of OPEs and PCBs in pig liver， respectively. Some OPEs were positively correlated with each other （r=0.278-0.841， P<0.05）， and all PCBs were positively correlated with each other （r=0.367-0.942， P<0.01）. The average EDI values of ∑7OPEs and ∑6PCBs from dietary intake of pig liver was 2.76 ng/kg·BW/d （P95=5.83 ng/kg·BW/d） and 0.28 pg/kg·BW/d （P95=0.58 pg/kg·BW/d）， respectively. And compared with the reference dose （RfD）， the HI values were far less than 1.ConclusionAlthough OPEs and PCBs are generally detected in pig liver， the pollution level is low. The dietary exposure risk of Hubei residents is relatively low.